Analisis Perbandingan Dua Software (Wireshark & Speedtest by Ookla) terhadap Pengukuran Quality of Service (QoS) pada Pengukuran Jaringan Provider Smartfren & Indosat Ooredoo di SMAN 3 Kota Serang - Didik Aribowo; Alwy Misbakhudin; Ririn Agustin; Muhammad Akmal Raihan; Fathan Mubinan Sugiatna; Egi Tri Saputra; Malika Azizah Faradila; Neng Tysha Nur Mahardiyanti; Muhammad Daffa Aldiansyah; Fakhri Malikal Azis; Varel Rizky Riansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the quality of internet networks provided by Smartfren and Indosat Ooredoo at SMAN 3 Kota Serang. The testing methods used include Wireshark, to monitor real-time network traffic, and Speedtest by Ookla, to measure download speed, upload speed, and latency. The results show that Indosat Ooredoo outperforms Smartfren in terms of both speed and connection stability. Speedtest offers a quick and user-friendly overview of network performance, while Wireshark provides more detailed technical data. Based on the measurements, Indosat Ooredoo is more suitable for supporting digital learning activities at the school due to its lower latency and higher access speed. Therefore, selecting the right internet provider plays a crucial role in ensuring smooth and effective internet-based learning.